The assassin [compact disc, unabridged] - Coonts, Stephen, 1946- (Macmillan Audio : Distributed by Macmillan, 2008)
Tommy Carmellini embarks on his most perilous mission yet when he is called in to help prevent a puzzling terrorist plot. What he doesn't know is that Al Qaeda leader Abu Qasim is willing to pay the New York mafia a small fortune in order to help him successfully carry out a massive terror attack. Can Tommy prevent this horrific plan, or will America be left in shock once again?